Counseling On How To Brush Your Teeth Properly And Properly In Sdn 08 Padang Sago - Syukri, Daimon; Rosyada, Inayah; Sharafa, Salwa Ash (Andalasian International Journal of Social and Entrepreneurial Development, 2025)
Oral health is an important aspect in maintaining children's health, especially during their growing years. Dental health problems, such as cavities, are still often found in children in Indonesia, which basically arise due to a lack of knowledge and proper brushing habits. This study aims to increase the awareness and understanding of students of SDN 08 Padang Sago regarding the urgency of maintaining oral health through educational activities. The program included the delivery of information about oral hygiene, demonstration of how to brush teeth properly, and tooth brushing practice accompanied by KKN UNAND students. The results of the training showed that about 80% of the students initially did not understand the importance of oral health, but after attending the counseling, they were able to understand and practice the correct way to brush their teeth. This program is designed to be an effective starting point in instilling healthy habits in caring for teeth and mouth from an early age. It is also suggested that this activity be continued so that it becomes a habit for students to take care of their dental health regularly